ANALISIS KOMPARATIF PEMIKIRAN KEUANGAN SYARIAH TAQI USMANI DAN YUSUF QARDHAWI - Tubagus A. Micail Farqu Sibqi; Husnul Khatimah; Hardiansyah, Hardiansyah (Journal of Innovation Research and Knowledge, 2025)
The thoughts of Taki Usmani and Yusuf Qardawi have had a great influence on the development of Indonesia's Islamic financial system. Both offer different but complementary perspectives to understand the principles of Islamic finance and their application in contemporary contexts. Taqi Usmani emphasized compliance with Sharia law, the importance of responsible investment management and the proper implementation of Sharia contracts. This approach is relevant to the Islamic finance industry in Indonesia, which aims to increase public trust through transparency and compliance. Yusuf Qardawi, on the other hand, emphasized the function of money as a productive medium of exchange and store of value, and encouraged ijtihad innovation to adapt Islamic law to the needs of modern society. He also emphasized the importance of implementing zakat as a tool to support the welfare of the community. These two ideas can complement each other to build an Islamic financial system that is not only in accordance with Islamic principles but also contributes to the welfare of the community. By applying the thinking of Maulana Taqi Usmani and Yusuf Al-Qardawi, Islamic finance as part of sharia control and regulations in Indonesia plays an important role in increasing its credibility and attractiveness in the eyes of the public and plays a positive role in sustainable economic development.